Union-Nonunion Wage Differentials in the Public Administration, Educational, and Private Sectors: 1970-1983 - Moore, William J.; Raisian, John (The Review of Economics and Statistics, 1987)
William J. Moore, John Raisian, Union-Nonunion Wage Differentials in the Public Administration, Educational, and Private Sectors: 1970-1983, The Review of Economics and Statistics, Vol. 69, No. 4 (Nov., 1987), pp. 608-616